1985
DOI: 10.1128/jvi.54.2.358-363.1985
|View full text |Cite
|
Sign up to set email alerts
|

Immortalization of rat embryo fibroblasts by an adenovirus 2 mutant expressing a single functional E1a protein

Abstract: Expression of the adenovirus Ela and Elb genes is required for transformation of nonpermissive rodent cells. Differential splicing of the Ela precursor RNA molecules results in the production of two early mRNAs, 13S and 12S, which encode a 289-amino-acid-residue (289R) and 243R protein, respectively. Previously we constructed a mutant virus, d1231, which can only produce normal 289R protein from the Ela gene. In this report we demonstrate that d1231 induced focal transformation of primary rat embryo fibroblast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

1986
1986
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Transformation efficiencies of p917-1227 and pXC1 (Ad5 El) were not significantly different, and p917-975 was approximately two-to threefold less efficient (data not shown), a characteristic which is shared by the hybrid p975, than p1227 and pHAB6 (22). Since the 12S splice donor site is not present in p975 or p917-975, the lower transforming efficiencies of these plasmids could be due to the lack of a 12S mRNA product, which is known to be important for transformation (16,19,20,22,23,26,28,31,32). These results and our previous observations (22) indicated that differences in transforming efficiencies between the EIA proteins of Ad5 and Adl2 are due to at least two regions of Adl2 EIA which result in decreased transformation efficiency.…”
Section: Residuementioning
confidence: 94%
“…Transformation efficiencies of p917-1227 and pXC1 (Ad5 El) were not significantly different, and p917-975 was approximately two-to threefold less efficient (data not shown), a characteristic which is shared by the hybrid p975, than p1227 and pHAB6 (22). Since the 12S splice donor site is not present in p975 or p917-975, the lower transforming efficiencies of these plasmids could be due to the lack of a 12S mRNA product, which is known to be important for transformation (16,19,20,22,23,26,28,31,32). These results and our previous observations (22) indicated that differences in transforming efficiencies between the EIA proteins of Ad5 and Adl2 are due to at least two regions of Adl2 EIA which result in decreased transformation efficiency.…”
Section: Residuementioning
confidence: 94%
“…These two proteins have been implicated to different degrees in the various functions attributed to region Ela. Both Ela gene products play roles in the transformation of rodent cells (16,19,26,41). The larger protein (289R protein) is necessary (4, 9, 30) and sufficient (27) for the enhancement of early viral gene expression during infection, but the smaller protein (243R protein) enhances viral DNA replication in growth-arrested cells (34).…”
mentioning
confidence: 99%
“…In transformed cells and at early times after infection, two families of ElA products are detected that are translated from two overlapping ElA mRNAs (13S mRNA and 12S mRNA) that differ only by the sizes of the introns removed during posttranscriptional processing. Expression of these ElA proteins is associated with several functions including either activation or repression of viral and cellular gene transcription (reviewed in reference 3), stimulation of viral and cellular DNA replication (24, 29), establishment of transformation (15,20), viral specificity of transformed cell tumor-specific transplantation antigen (26), and induction of susceptibility of virus-infected (5) and virus-transformed (6) cells to the cytolytic effects of NK cells and activated macrophages. Studies of the intracellular localization of ElA proteins indicate that proteins that contain the carboxyterminal 5 amino acids encoded by the ElA gene localize to the nucleus (19).…”
Section: Resultsmentioning
confidence: 99%
“…The viral protein components of CTL target structures in these studies appeared to map to adenovirus early transcriptional regions 1 (El [25]) and 3 (E3 [18]). The adenovirus El region comprises the ElA and E1B genes and encodes nonstructural viral proteins that are involved in viral transcription, replication, and transformation of mammalian cells (15,20,23). Although ElA proteins have not been reported to be associated with cell membranes, the E1B 15-kilodalton protein and a 19-kilodalton protein encoded by the E3 gene have been associated with membranes in adenovirus-infected and transformed cells, and the E3 19-kilodalton protein has been shown to be associated with the cellular class I major histocompatibility antigen (18,22).…”
mentioning
confidence: 99%